The Additional Economic Burden of Frailty in Adult Cervical Deformity Patients Undergoing Surgical Intervention. Issue 20 (15th October 2022) - Passias, Peter G.; Kummer, Nicholas A.; Williamson, Tyler K.; Ahmad, Waleed; Lebovic, Jordan; Lafage, Virginie; Lafage, Renaud; Kim, Han Jo; Daniels, Alan H.; Gum, Jeffrey L.; Diebo, Bassel G.; Gupta, Munish C.; et al.
Abstract : Summary of Background Data: The influence of frailty on economic burden following corrective surgery for the adult cervical deformity (CD) is understudied and may provide valuable insights for preoperative planning. Objective: To assess the influence of baseline frailty status on the economic burden of CD surgery Study Design: Retrospective cohort. Materials and Methods: CD patients with frailty scores and baseline and two-year Neck Disability Index data were included. Frailty score was categorized patients by modified CD frailty index into not frail (NF) and frail (F). Analysis of covariance was used to estimate marginal means adjusting for age, sex, surgical approach, and baseline sacral slope, T1 slope minus cervical lordosis, C2–C7 angle, C2–C7 sagittal vertical axis. Costs were derived from PearlDiver registry data. Reimbursement consisted of a standardized estimate using regression analysis of Medicare payscales for services within a 30-day window including length of stay and death. This data is representative of the national average Medicare cost differentiated by complication/comorbidity outcome, surgical approach, and revision status. Cost per quality-adjusted life-year (QALY) at two years was calculated for NF and F patients. Results: There were 126 patients included. There were 68 NF patients and 58 classified as F. Frailty groups did not differ by overall complications, instance of distal junctional kyphosis, or reoperations (all P >0.05). These groups had similar rates of radiographic and clinical improvement by two years. NF and F had similar overall cost ($36, 731.03 vs. $37, 356.75, P =0.793), resulting in equivocal costs per QALYs for both patients at two years ($90, 113.79 vs. $80, 866.66, P =0.097). Conclusion: F and NF patients experienced similar complication rates and upfront costs, with equivocal utility gained, leading to comparative cost-effectiveness with NF patients based on cost per QALYs at two years. Surgical correction for CD is an economical healthcare investment for F patients when accounting for anticipated utility gained and cost-effectiveness following the procedure. Level of Evidence: III.